Assessment of Brain Drain and its Impact on the Sending Economy: A Case Study of Nepal - Silwal, Apresha (The International Research Journal of Management Science, 2019)
The research attempts to examine the factors that lead the experts to leave the country. Using 160 respondents living abroad, the study investigates the relationship between brain drain and the sending economy i.e. Nepal. The study follows descriptive, co-relational and causal comparative research design to analyze the purpose of this study. The result reveals that people leave country mainly for the purpose of education, employment and skills but what makes them settle there is employment and skills, as both of them have significant impact on sending economy at 5 per cent level of significant. As people get better job offers, they start working abroad and when they realize their skills being enhanced, their chances of getting settled in foreign land increases. This means as long as they realize self-growth in the form of better jobs and good skills, they do not plan to come back.